Comparison of head impact location during games and practices in Division III men's lacrosse players. (March 2017) - O'Day, Kathleen M.; Koehling, Elizabeth M.; Vollavanh, Lydia R.; Bradney, Debbie; May, James M.; Breedlove, Katherine M.; Breedlove, Evan L.; Blair, Price; Nauman, Eric A.; Bowman, Thomas G.
Abstract: Background: Head impacts have been studied extensively in football, but little similar research has been conducted in men's lacrosse. It is important to understand the location and magnitude of head impacts during men's lacrosse to recognize the risk of head injury. Methods: Descriptive epidemiology study set on collegiate lacrosse fields. Eleven men's lacrosse players (age = 20.9 ± 1.13 years, mass = 83.91 ± 9.04 kg, height = 179.88 ± 5.99 cm) volunteered to participate. We applied X2 sensors behind the right ear of participants for games and practices. Sensors recorded data on linear and rotational accelerations and the location of head impacts. We calculated incidence rates per 1000 exposures with 95% confidence intervals for impact locations and compared the effect of impact location on linear and rotational accelerations with Kruskal-Wallis tests. Findings: We verified 167 head impacts (games = 112; practices = 55). During games, the incidence rate was 651.16 (95% confidence interval = 530.57–771.76). The high and low incidence rates for head impact locations during games were: side = 410.7 (95% confidence interval = 292.02–529.41) and top = 26.79 (95% confidence interval = 3.53–57.10). For games and practices combined, the impact locations did not significantly affect linear ( χ 2 3  = 6.69, P  = 0.08) or rotational acceleration ( χ 2 3  = 6.34, P  = 0.10). Interpretation: We suggest further research into the location of head impacts during games and practices. We also suggest player and coach education on head impacts as well as behavior modification in men's lacrosse athletes to reduce the incidence of impacts to the side of the head in an effort to reduce potential injury. Highlights: Head impacts have been widely studied in football, but there is little research for men's lacrosse. The side of the head was the most common location for impacts across games and practices. Further research is encouraged as well as officials, coach, and player education.